The Influence of Store Atmosphere, Service Quality, WOM, and Price Perception on Purchase Decisions of Balinese Traditional Attire : A Study on Consumers of Cahya Busana, Canggu Branch - Ni Kadek Jesika Noviana Agustin; Ni Made Wulandari Kusumadewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the influence of store atmosphere, service quality, word of mouth (WOM), and price perception on consumer purchasing decisions at Cahya Busana's Canggu branch, a local Balinese MSME specializing in high-quality traditional Balinese clothing for men, women, and children. With an increasing demand for traditional attire, understanding the factors that influence consumer decisions is vital for business growth. The study targeted consumers who had purchased traditional clothing at the Canggu branch, using non-probability sampling to select 110 respondents. The data analysis was conducted through multiple linear regression, assisted by SPSS software, to evaluate the relationship between the independent variables (store atmosphere, service quality, WOM, and price perception) and the dependent variable (consumer purchase decisions). The findings indicate that all four factors—store atmosphere, service quality, WOM, and price perception—positively and significantly impact consumers’ purchasing decisions. Specifically, a pleasant store atmosphere, high-quality service, positive word-of-mouth recommendations, and favorable price perception were found to enhance consumers' likelihood of purchasing traditional Balinese clothing. The results suggest that MSMEs, particularly in the traditional clothing sector, can leverage these factors to boost consumer confidence and drive sales. This study contributes valuable insights for businesses aiming to improve their purchasing processes by focusing on these key variables to increase consumer satisfaction and decision-making. By understanding these influences, Cahya Busana and similar businesses can optimize their strategies to attract and retain customers, ultimately improving their market position.